An integrated communications campaign on the aging issue in Singapore. - Koh, Jeffrey Hien Kiat. (2009)
To address the lack of public awareness regarding the severity of an aging population in Singapore by 2030, this paper examines the possibility of instituting an integrated communications campaign as a complementary solution to present government policies. Preliminary research concludes that there is a need for Singaporeans to be aware of the problems of an aging society. As a solution, our campaign involves the use of print, television, radio and event management in a concreted approach to address a national audience. In view of the fact that the Ministry of Community Development is considering a more comprehensive, holistic and integrated approach in dealing with the aging problem, the proposed campaign will be recommended to the ministry. This is a pilot effort in generating greater national consciousness and promoting the need for the individual to prepare for elderly independence today.